Geração de valor: incorporação e fusão em uma empresa de engenharia consultiva. Um estudo de caso com a empresa ARCADIS - Albuquerque Junior, Marcos Matos Brito de (2014)
The object of this dissertation is to analyze the influence of net revenue, total shareholders' equity and long-term debt on the profitability of the value of the shares of ARCADIS, by applying methods of time series, such as unit root test, test Johansen cointegration, the vector autoregression model (VAR), vector error correction (VEC), impulse response and variance decomposition of forecast errors function. The database is quarterly from January 2000 to December 2012 According to the Johansen cointegration test, the results indicate that the series that have unit roots are all integrated of order one in level and show a relationship term between them. The coefficients in the estimated model is presented according to the literature;can also observe that the tests demonstrated a strong influence of net revenue on the share value when compared with the other variables. From the evaluations performed in this study, it can be stated that the variables are relevant to explain the variations over time in the dependent variable value of the share on the stock exchange. That paper presents an analysis of the evolution of consulting engineering companies and the increasing degree of internationalization. Highlights the relevance of the study compared with the purpose of understanding the growth of the company ARCADIS in consulting engineering and project management segment. And since expanded its market competitiveness.